Analysis Figurative Language “Let Me Not To The Marriage Of True Minds” By William Shakespeare’s - Ristin Dwi Herlinawati; Fairuz Mufidah (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Literary works are creations written with the aim of conveying an aesthetic impression. Literary works can take the form of prose, poetry, or drama. To make poetry more beautiful and easier to understand, a writer needs to understand the rules for creating good poetry. This research aims to analyze the various types of figurative language found in William Shakespeare's poem titled